Analisis bibliometrik perkembangan penelitian tentang perjuangan ulama menggunakan Vosviewer - Darmawan, Budi; Shalihin, Nurus; Nopriyasman, Nopriyasman (Daluang: Journal of Library and Information Science, 2023)
Purpose. This research aims to investigate the prominent Ulama figures who have played significant leadership roles in Indonesian society throughout history. These Ulama have been instrumental in various aspects, including social, political, and religious realms. The article delves into the evolution of research publications related to the struggles of Ulama from 2010 to 2023.Methodology. The method employs a descriptive bibliometric analysis focused on the struggle of Ulama, using specific keywords like “Perjuangan” and “Ulama” on the Dimensions platform, within the timeframe of 2010 to 2023.Results and discussion. The results reveal fluctuations in the number of publications, ranging from a peak of 786 in 2018 to only 70 in 2023, with a significant spike in 2017. The research network involves three clusters of authors, highlighting diversity in the field. Overlay Visualization demonstrates strong author relationships, with some forming influential networks. The Indonesian Institute of Science had a notable impact on many writers. Density Visualization identifies active authors and Co-occurrence analysis reveals four keyword clusters, with “Islam” and “Indonesia” as primary foci. A trend shift occurred in 2020, with new keywords gaining prominence such as “Education, Women, Politic, and Law”. These data shows that research on the theme of the ulama's struggle still has many opportunities.Conclusions. The bibliometric analysis of ulama struggle research (2010-2023) provides information about publication fluctuations, close collaboration. Diversity, changing trends, and research potential that has not yet been fully explored regarding the struggles of ulama  is used to encourage and determine the focus for further research on the struggles of ulama.